English adverbial relative clauses: A new angle in the English as a foreign language classroom - Chaohai Lin; Nur Rasyidah Mohd Nordin; Hariharan N. Krishnasamy (Institute of Advanced Engineering and Science, 2023)
Intralingual comparison in language learning is an effective teaching method, which introduces a new learning from what students have mastered to what they are going to learn. The study is to investigate the effects of applying intralingual comparison on the teaching of English adverbial relative clauses to Chinese Senior high school students. Data was collected utilizing both quantitative and qualitative methods in a mixed method design. Data was gathered via experimental research (n=103) and semi-structured interview (n=12). The experimental group’s posttest scores improved statistically significantly after intervention. Research findings suggest that applying intralingual comparison in teaching could be considered as an effective teaching method in improving students’ performance on learning English adverbial relative clauses. Besides, students would have more active and positive attitudes toward learning adverbial relative clauses than the traditional teaching method.